Intraspecific Variation in a Scorpionfly Newly Recorded from Texas and the State of Taxonomy of North American Panorpidae (Mecoptera) - Joshua R. Jones (Psyche: A Journal of Entomology)
Panorpa vernalis Byers is recorded for the first time from Texas, and represents only the second species of Panorpa documented from the state. Intraspecific variations between the Texas specimens and Byers' original description are discussed. A synopsis of the principal modern keys for identification of North American Panorpa is provided, and an argument for a modern taxonomic review of the Panorpidae of North America is presented.